how can i proof that >>>>>> p(A | B') = p(A | B)(adsbygoogle = window.adsbygoogle || []).push({});

well i tried but i think there is a hole in the solution T.T

if we said that

p(A|B)=p(A&B)/p(B)

p(A|B')= p(A&B')/p(b')

= p(A) - p(A&B)/1-p(B)

so0o0o how can i complete it ??

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Probability proof

Loading...

**Physics Forums | Science Articles, Homework Help, Discussion**